Использование информационно-коммуникационной технологии с элементами программированного обучения в преподавании дисциплин психологического цикла - Калиниченко, О.В.; Назмутдинов, Р.А. (My University, 2016)
Article is devoted to opportunities of use of information and communication technologies within teaching disciplines of a psychological cycle. Justification of relevance of the declared problem is given. Functions of information and communication technologies and the requirement to development of courses with use of ICT are given. The types of electronic textbooks are described. Information on the actual use of information and communication technologies in the course of teaching psychological disciplines is provided.
Keywords: Information; Information and Communication Technologies; programmed instruction; electronic textbook; higher education